Effects of Withania somnifera (Ashwagandha) and Terminalia arjuna (Arjuna) on physical performance and cardiorespiratory endurance in healthy young adults - Sandhu, Jaspal Singh (Medknow Publications, 2010)
INTRODUCTION: Several medicinal plants have been described to be beneficial for cardiac ailments in Ayurveda like Ashwagandha and Arjuna. Ashwagandha-categorised as Rasayanas, and described to promote health and longevity and Arjuna primarily for heart ailments. coronary artery disease, heart failure, hypercholesterolemia, anginal pain and can be considered as a useful drug for coronary artery disease, hypertension and ischemic cardiomyopathy. OBJECTIVE: There are no scientific clinical studies showing effect of both these drugs on exercise performance after regular administration when given as supplements The present study was therefore designed and performed to assess the effects of Withania somnifera (Ashwagandha) and Terminalia arjuna (Arjuna) individually and as a combination on maximum velocity, average absolute and relative Power, balance, maximum oxygen consumption (VO2 max) and blood pressure in humans. MATERIALS AND METHODS: Forty normal healthy. Subjects (either sex, mean age 20.6 ± 2.5yrs and mean Body Mass Index 21.9 ± 2.2) were recruited after written informed consent was obtained. Institutional Ethics Committee permission was also obtained. Thirty participants were assigned to experimental group of which 10 received standardized root extracts of Withania somnifera, 10 received standardized bark extract of Terminalia arjuna and the rest of the 10 received standardized root extract of Withania somnifera in addition to bark extract of Terminalia arjuna both. Both the drugs were given in the form of capsules (dosage 500mg/day for both the drugs). Ten participants received placebo (capsules filled with flour). All the subjects continued the regimen for 8 weeks. All variables were assessed before and after the course of drug administration OBSERVATIONS: Our study showed that Withania somnifera increased velocity, power and VO2 max whereas Terminalia arjuna increased VO2 max and lowered resting systolic blood pressure. When given in combination, the improvement was seen in all parameters except balance and diastolic blood pressure. CONCLUSION: Withania somnifera may therefore be useful for generalized weakness and to improve speed and lower limb muscular strength and neuro-muscular co-ordination. Terminalia arjuna may prove useful to improve cardio-vascular endurance and lowering systolic blood pressure. Both drugs appear to be safe for young adults when given for mentioned dosage and duration.